IMPLEMENTASI KEBIJAKAN PROGRAM PENDIRIAN BADAN USAHA MILIK DESA (BUMDES) DALAM USAHA MENINGKATKAN KUALITAS HIDUP SOSIAL EKONOMI MASYARAKAT: Studi Kasus Badan Usaha MilikDesa Di Landungsari Kecamatan Dau Kabupaten Malang Provinsi JawaTimur - Hadiwiyono Hadiwiyono; Adi Roy Adi Roy Pandang (STIA MALANG, 2023)
Village is an administrative division in Indonesia under a sub-district headed by the Village Head. Therefore, inthe East Java region, especially the Landungsari Village Government, Dau District realizes that LandungsariVillage-Owned Enterprises are good and of course must be managed properly so as to improve the quality ofsocial life of the community. The purpose of this study is to find out how the implementation of the village-ownedenterprise establishment program in improving the quality of social life of the community, to find out who isinvolved in the establishment of a Village-Owned Enterprise and to find out what factors affect the implementationof the village-owned enterprise establishment program in improving the quality of social life of the community.Implementation is implemented when a policy is formulated with clear objectives. Therefore, to find out theImplementation of the Village Owned Business Entity Establishment Program Policy (Bumdes) in an Effort toImprove the Quality of Social Life of the Community, to obtain data, data collection techniques by conductingInterviews, Documentation, and Observation, researchers use the type of Descriptive research with a Qualitativeapproach. Based on the Results of Research in Landungsari Village Regarding the Implementation of the Policyfor the Establishment of Village-Owned Enterprises (BUMDes) Program in an Effort to Improve the Quality ofSocial Life of the Community, it can be concluded that for now the efforts of the Landungsari Village Governmenthave run well and optimally, because the Landungsari Village Government has invited the community to worktogether in terms of maintaining and protecting all businesses that have been managed by Business Entity officers Village Owned both in terms of business implementation of Market Business Units, Agricultural Units, Livestock,Industrial Hum, Waste Management, and Savings and Loans Business Units as a form of empowering villagecommunities so that rural communities can increase income or income through market business programs.